If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(2x + 5) = 2 Reorder the terms: -2(5 + 2x) = 2 (5 * -2 + 2x * -2) = 2 (-10 + -4x) = 2 Solving -10 + -4x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -4x = 2 + 10 Combine like terms: -10 + 10 = 0 0 + -4x = 2 + 10 -4x = 2 + 10 Combine like terms: 2 + 10 = 12 -4x = 12 Divide each side by '-4'. x = -3 Simplifying x = -3
| 8+1=-3(3x-3) | | (64^(1/3))(128^(2/7)) | | 4x-8y=-7 | | -5x^2+30x-25=0 | | 4x=3(4-y) | | 5p=11/2x2/3 | | 3(2x-5)=6(x-4)+x | | H+9=55 | | r-8.9=-8.3 | | 4(x-4)=-6(x+1)+46 | | d-9=11 | | -8x-(4yi)=12i+24 | | 8w+12=37.8 | | 24=n+13 | | X^2+y-49=0 | | 6x-12=30x | | 8-w=21 | | 2(x-1)+4x=-20 | | 0.7-0.36= | | -27n+6-2n+17=37+3n+3n | | 50+0.20=30+0.70 | | D=(r+c)t | | x=-2x+8 | | i+13=27 | | -1/1=4/8 | | 5(x-3)-x=1 | | 3x-10+2x=90 | | x^2-4x=a | | f(x)=x^2-5x-5 | | 15x+-6= | | 8p+56p=0 | | 10x^2+31x-63=0 |